1992
DOI: 10.1111/j.1469-8137.1992.tb02944.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring investment in carnivory: seasonal and individual variation in trap number and biomass in Utricularia vulgaris L.

Abstract: SUMMARYThe partitioning of biomass between traps and leaves is a measure of the investment in carnivory of Utricularia vulgaris and is dependent on the relative values of three attributes: trap size, trap number and leaf size.Marked seasonal and individual variations in trap size, trap number and leaf size occur within a small population of U. vulgaris at Wicken Fen, Cambridgeshire, UK, with some plants consistently having fewer traps per leaf than others, and some smaller leaves than others, throughout the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 7 publications
1
32
1
1
Order By: Relevance
“…Shoot growth (extension) rates recorded in the present paper (Fig. 2) are comparable with other published values for Aldrovanda or Utricularia vulgaris (FRIDAY 1989, 1992, KOMIYA & SHIBATA 1998, ADAMEC 2000. The considerable variation in biomass doubling times between enclosures (Aldrovanda 8.4-21.5 days, Utricularia 9.1-33.2 days; Table 3) could still be partly due to differences between initial plant biomasses.…”
Section: Discussionsupporting
confidence: 92%
“…Shoot growth (extension) rates recorded in the present paper (Fig. 2) are comparable with other published values for Aldrovanda or Utricularia vulgaris (FRIDAY 1989, 1992, KOMIYA & SHIBATA 1998, ADAMEC 2000. The considerable variation in biomass doubling times between enclosures (Aldrovanda 8.4-21.5 days, Utricularia 9.1-33.2 days; Table 3) could still be partly due to differences between initial plant biomasses.…”
Section: Discussionsupporting
confidence: 92%
“…Here the individual traps on a plant are the functional equivalent of individual cells with their single phagotrophic apparatus in protistan phagotrophic phototrophs. The allocation to traps in the aquatic species of Utricularia can amount to 50% of the biomass, with a considerable variation in volume (25-fold) of individual traps on the same plant (Friday 1991(Friday , 1992. Contradicting initial expectations, Knight and Frost (1991) showed that Utricularia produced more traps when the nutrient concentration in lake water was higher.…”
Section: Evolutionary Costs That May Offset the Benefits Of Phagotropmentioning
confidence: 99%
“…Each axis produces alternate, finely divided, four-lobed leaves (Taylor, 1989) in a linear age sequence. Each leaf bears a cohort of 30-150 suction traps, ranging in size from about 1 mm to more than 5 mm in length (Friday, 1991(Friday, , 1992. The plants studied grow in a clay pond at Wicken Fen, Cambridgeshire, 52° 18' N, 0° 17' E. The pH of the water is 7-8~8-4, the nitrate-N less than 2 mg r^ and orthophosphate-P less than 5-0/igl"t hroughout the year.…”
Section: Plant Characteristicsmentioning
confidence: 99%